Pelatihan pembuatan modul ajar bagi guru SMA/SMK di Tebing Tinggi - Nila Kesumawati; Destiniar Destiniar; Dina Octaria; Yunika Lestaria Ningsih; Putri Fitriasari; Anggria Septiani Mulbasari; Tika Dwi Nopriyanti; Allen Marga Retta (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2021)
Improving the quality of learning in schools is carried out by various strategies, one of which is developing teaching materials. The development of teaching materials in modules is currently a very urgent need. Because the application of the module can make learning activities more well-planned, independent, complete, and precise results so that educators can assist schools in realizing quality learning. However, in reality, many educators have difficulty making teaching modules that suit the needs of students. Due to educators' lack of knowledge and training to make teaching modules. Therefore, this PKM activity aims 1) to introduce and equip educators about teaching modules, 2) to assist educators in making teaching modules. The implementation method used in this activity is lecture, practice, and discussion. The activities were conducted online using the Zoom application and offline at SMA Negeri 2 Tebing Tinggi Empat Lawang. The steps in PKM activities are 1) preparation, 2) implementation, 3) reflection. Data was collected through a questionnaire. The implementation of PKM activities showed that the training activities ran smoothly, and the participants were enthusiastic about participating in the training. From the results of data analysis, it can be concluded that 72.8% of the participants stated that this training activity could increase their knowledge and understanding of the module, and 83.3% stated that this training activity could train the skills of educators in doing modules. This activity can contribute to educators producing practical modules to use in the learning process